Pengaruh Harga Canang dan Pendapatan Konsumen Terhadap Permintaan Canang di Desa Sanur - Dewi, Putri Shinta; Sukarsa, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Canang is a Hindu religious ceremony means. This study is aimed at finding out the influence price of canang and the income consumers toward the demand for canang and the nature of price elasticity of canang and income. The study used proportionate stratified random sampling on 97 families, The analysis by using regression model double’s log equation. The result indicates that the price of canang during the commond day and good day have positively significant influence toward the demand for canang , but on celebration day no effect and the income of consumer on the common day, good day and  celebration day have positively significant influence. The nature of price elasticity of canang is inelastic and income elasticity showed normal goods .
Keywords: Demand for canang; Elastisity; Common day; Good day and Celebration day